(untitled) (KULT_online, 2012)
In her dissertation published by Wissenschaftlicher Verlag Trier Stefanie Albers analyses verbally evoked intermedial phenomena in contemporary anglophone literature. She concentrates on literary works in which the theme of the visual arts is deliberately applied in order to negotiate aesthetic and social questions. Accordingly, the author demonstrates that intermediality not only fulfils narratological functions; Albers also points out that those hybrid texts can be read as evaluations of extra-narrative issues and as socio-cultural commentaries on our postmodern world.